UTILIZATION THE QUALITY OF DURIAN SKIN BRICKETS AS AN ENVIRONMENTALLY FRIENDLY TECHNOLOGY ALTERNATIVE - Ega Dwi Permata Sari; Iwan Setiawan; Rendy Wikrama Wardana; Euis Nursaadah (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
Durian skin briquettes can be used as an alternative energy product environmentally friendly technology, cause the potential for durian skin waste is still very large in Bengkulu. The research objective focuses on testing the quality of Durian Skin Briquettes as an alternative environmentally friendly technology. The type of research is experimentation, with the independent variable namely durian skin briquettes, the control variables namely heating value, water content and grade. Data collection techniques were carried out by observing the potential for durian skin in Bengkulu. The data analysis method this research involves quantitative data analysis. Durian skin briquettes are divided into 2 groups: A1 (90% yellow durian skin charcoal: 10% adhesive), A2 (90% green durian skin charcoal: 10% adhesive). Durian skin briquette test results comparing 90% green durian skin charcoal with 10% adhesive showed the best results with a total heat of 4748 k cal/kg. Meanwhile, a ratio of 90% yellow durian skin charcoal to an adhesive ratio of 10% produces a total heat of 4670 K cal/kg. The conclusion of this research is that the quality test of durian skin briquettes as an alternative environmentally friendly technology shows the best results with a heat amount of 4748 k cal/kg in green durian skin briquettes.